2008
DOI: 10.1007/s11695-007-9344-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Panniculectomy and Ventral Hernia Repair Following Weight Reduction after Gastric Bypass Surgery: Is it Safe?

Abstract: Following obesity surgery, simultaneous ventral hernia repair and panniculectomy can be accomplished safely with short hospital stays and few in-hospital complications. Postoperative wound problems are not infrequent but can be managed in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…The existing experience when performing concomitant LVHR and LRYGBP and the use of biomaterials for the morbidly obese population have been controversial [18]. However, some studies have showed that following obesity surgery, simultaneous ventral hernia repair and panniculectomy can be accomplished safely with short hospital stays and few in-hospital complications, and this is independent of the mesh material used [19]. Postoperative wound problems are not infrequent but can be managed in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…The existing experience when performing concomitant LVHR and LRYGBP and the use of biomaterials for the morbidly obese population have been controversial [18]. However, some studies have showed that following obesity surgery, simultaneous ventral hernia repair and panniculectomy can be accomplished safely with short hospital stays and few in-hospital complications, and this is independent of the mesh material used [19]. Postoperative wound problems are not infrequent but can be managed in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Panniculectomy is association with increased risk of wound complication [7], with up to 31 % of wounds requiring sharp debridement postoperatively [8], and postoperative wound breakdown requiring treatment in 18 % of patients [9]. Currently, a surgeon's clinical judgment is considered the gold standard for identification of underperfused skin and soft tissue after panniculectomy or elevation of wide skin flaps for CST; the high frequency of complications indicates that this is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…3,15 This is probably affected by the nutrition deficiency and micro-architecture changes of the skin that alter immunity and integrity of the skin through different mechanisms. 16 In the current study, our overall complication rate was high, approaching half of our patients (49% of patients). There were no thromboembolic events and no mesh had to be removed; no mortality has been recorded.…”
Section: Discussionmentioning
confidence: 52%